Sero-prevalence of hepatitis B virus antigen and main Risk factors among people in Abu-Hamad locality River Nile State 2021 - 1. Asia Ali Ahmed Mohammed; 2. Fatima Ismail Hassan Omer; 3. Safia Abd- Elaziz Ahmed Ali; 4. Sahar Abass Abd-Alrahim Seid-Ahmed; 5. Shroug Ali Suliman Ali; 6. Mohammed Bakhit Adam Rahamat-Allah (جامعة الشيخ عبدالله البدري, 2021)
Abstract Hepatitis B virus also known as serum hepatitis , has incubation period 2 – 6 months. Infection occurs by direct inoculation or by contamination of mucous membranes. It may be self-limiting or develop to cause hepatocellular carcinoma [HCC] that cause death in regions where HBV is endemic and neonatal infection is common. The study aim to determine the sero-prevalence of hepatitis B virus antigen and main risk factors among people in Abu-Hamad locality River Nile state 2021. A cross-sectional study design conducted to collect information from 384 participant selected randomly from Abu-Hamad locality in River Nile state during the period , June to August 2021, through questionnaire by offering a number of questions relevant to the objectives of the study . The statistical analysis was performed by SPSS version 14.The study reflect that 18.5% of participants results were positive for hepatitis B virus, and found association between infected with HBV and some risk factors like: age, residence, alcohol drinking, whipping, etc. The prevalence of Hepatitis B virus in Abu-Hamad is high and the risk factor whipping is associated with infection. Health education to eliminate whipping in social events should be promoted. IV الخلاصة فيروس إلتهاب الكبد الوبائي النوع (ب) ‘ يعرف أيضاً بإلتهاب الكبد المصلي ‘ مدة حضانته من 2 -6 شهور . تحدث العدوى عن طريق الحقن المباشر أو تلوث الأغشية المخاطية. يمكن أن يكون زاتي الشفاء أو يتطور إلى سرطان الخلية الكبدية الذي يسبب الوفاة في المناطق التي يكون فيها فيروس الكبد الوبائي النوع (ب) متوطن وإصابة حديثي الولادة شائعة . تهدف الدراسة لتحديد معدل الإنتشار المصلي لفيروس إلتهاب الكبد الوبائي النوع(ب) وعوامل الخطورة الرئيسية على سكان محلية أبو حمد بولاية نهر النيل 2021 . تم إجراء الدراسة بتصميم مقطع مستعرض وقد تم جمع المعلومات من 384 مشارك تم إختيارهم عشوائياً من سكان محلية أبو حمد بولاية نهر النيل خلال الفترة من شهر يونيو حتى أغسطس 2021 ‘ من خلال إستبيان يعرض عدد من الأسئلة ذات الصلة بأهداف الدراسة . تم تنفيذ التحليل الإحصائي بإستخدام برنامج التحليل الإحصائي النوع (14). تعكس الدراسة أن 18.5% من نتائج المشاركين كانت إيجابية لفيروس إلتهاب الكبد الوبائي من النوع (ب) ‘ ووجدت علاقة بين الإصاية بفيروس إلتهاب الكبد الوبائي النوع (ب) وبعض عوامل الخطورة مثل : العمر ‘ السكن ‘ شراب الكحول ‘ الجَلِد ‘ إلى آخره . خلصت الدراسة إلى أن معدل إنتشار فيروس الكبد الوبائي النوع (ب) في محلية أبوحمد مرتفع ‘ وعامل الخطورة الجَلِد له علاقة بالإصابة بهِ . يجب تعزيز التوعية الصحية لإزالة عادة الجَلِد في المناسبات الإجتماعية .